Implementasi Metode Pembelajaran Inkuiri Dalam Merdeka Belajar Untuk Meningkatkan Prestasi Belajar Siswa - Rina Febrian; Muhtadin; Miftahul Huda (Gunung Djati Conference Series, 2022)
This study aims to determine the implementation of students in Merdeka Belajar through inquiry learning. The method used in this study is a literature study sourced from research that has been published by previous researchers. The results of this analysis can be concluded that the implementation of the Merdeka Belajar policy can affect student learning achievement because it can give students the right to grow and develop according to their needs and times. Of course, this resquires the role of the teacher to recognize the talents and interests of students so that they can implement Merdeka Belajar. To develop Independent Learning in inquiry learning applied by teachers to students, namely: 1) Planning to carry out inquiry learning; 2) Finding the information (Retrieving) needed; 3) Creating every information that has been obtained; 4) Sharing the information that has been obtained is then conveyed to the audience; 5) Evaluating the inquiry process that has been carried out.